Flame-made single phase Zn2TiO4 nanoparticles - Siriwong C. (2014)
Using zinc naphthenate and titanium tetra isopropoxide (1:1 mol.%) dissolved in ethanol as precursors, single phase Zn2TiO4 nanoparticles were synthesized by the flame spray pyrolysis technique. The Zn2TiO4 nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS). The BET surface area (SSABET) of the nanoparticles was measured by nitrogen adsorption. The average diameter of Zn2TiO4 spherical particles was in the range of 5 to 10 nm under 5/5 (precursor/oxygen) flame conditions. All peaks can be confirmed to correspond to the cubic structure of Zn 2TiO4 (JCPDS No. 25-1164). The SEM result showed the presence of agglomerated nanospheres with an average diameter of 10-20 nm. The crystallite sizes of spherical particles were found to be in the range of 5-18 nm from the TEM image. An average BET equivalent particle diameter (d BET) was calculated using the density of Zn2TiO 4. © 2011 Elsevier B.V. All rights reserved.